Exploring perceptions of marine biosecurity interventions: insights from the commercial marina sector. (August 2020) - Vye, Siobhan R.; Wynne-Jones, Sophie; Masterson-Algar, Patricia; Jenkins, Stuart R.
Abstract: Recreational boating is a largely unregulated vector of non-native species and contributes to both initial introduction and secondary spread. As such, marinas and ports often experience high propagule pressure and are hotspots of non-native species. In many countries, there is little or no legal requirement for marinas to implement biosecurity in day-to-day operations to reduce the risk of non-native species introduction. Instead, biosecurity is often encouraged and implemented voluntarily meaning uptake may be limited. To understand the range of perceptions of biosecurity within the marina sector, focus groups were conducted as part of a workshop attended by operators from Ireland and Wales. In the first focus group, participants discussed the barriers and drivers to the overall process of designing a biosecurity plan for a marina. A second focus group asked participants to identify strengths and weaknesses of a range of biosecurity tools, such as risk assessments and in-water quarantine berths. Thematic analysis revealed lack of financial resources, in combination with doubt regarding the effectiveness of biosecurity interventions, to be the greatest barriers to uptake. Aligning with good practice and the perceived benefits of a clean environment for business were seen as drivers. Integrating biosecurity into normal marina operations requires bottom up and top down support from customers and relevant authorities respectively. We recommend that alongside testing the effectiveness of biosecurity interventions, researchers should also present robust evidence of cost-effectiveness, and consider and address any potential effects on marina businesses. Highlights: Recreational boating is a vector for non-native species at local, regional and global scales. Marinas are hotspots for non-native species yet biosecurity is often voluntary. Marina operators identified cost and doubt of effectiveness as barriers to biosecurity. Alignment with good practice and maintaining the environment were drivers for biosecurity. Bottom-up and top-down support is required to integrate biosecurity into marina operations.